2007
DOI: 10.1038/nsmb1339
|View full text |Cite
|
Sign up to set email alerts
|

A regulator of Dscam mutually exclusive splicing fidelity

Abstract: The Down syndrome cell adhesion molecule (Dscam) gene has essential roles in neural wiring and pathogen recognition in Drosophila melanogaster. Dscam encodes 38,016 distinct isoforms via extensive alternative splicing. The 95 alternative exons in Dscam are organized into clusters that are spliced in a mutually exclusive manner. The exon 6 cluster contains 48 variable exons and uses a complex system of competing RNA structures to ensure that only one variable exon is included. Here we show that the heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 33 publications
2
99
0
1
Order By: Relevance
“…While the mechanism of mutually exclusive splicing has been studied in both the exon 4 (Kreahling and Graveley 2005) and exon 6 clusters (Graveley 2005;Anastassiou et al 2006;Olson et al 2007), the mechanism is only well understood for the exon 6 cluster. Mutually exclusive splicing within the exon 6 cluster involves the formation of competing RNA secondary structures between selector sequences located upstream of each variable exon and a single docking site located between exon 5 and the first exon 6 variant (Graveley 2005;Anastassiou et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanism of mutually exclusive splicing has been studied in both the exon 4 (Kreahling and Graveley 2005) and exon 6 clusters (Graveley 2005;Anastassiou et al 2006;Olson et al 2007), the mechanism is only well understood for the exon 6 cluster. Mutually exclusive splicing within the exon 6 cluster involves the formation of competing RNA secondary structures between selector sequences located upstream of each variable exon and a single docking site located between exon 5 and the first exon 6 variant (Graveley 2005;Anastassiou et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…6 Several trans-acting factors and multiple cis-elements have been demonstrated to regulate the mutually exclusive exons in cultured insect and mammalian cells. [7][8][9][10][11][12][13][14][15][16] Several mechanisms have been proposed to direct mutually exclusive splicing, including steric interference, 17 spliceosome incompatibility, 18 nonsense-mediated decay, 6 and competing RNA secondary structures. [19][20][21][22] However, the underlying regulatory mechanisms in large part remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the process of Dscam and 14-3-3ζ variable exon choice in D. melanogaster relies on a combination of alternative RNA structure and repressors, which act in concert to activate a variable exon. 14,22 First, the latter arrangement would be advantageous when considering the evolutionary expansion from the two-duplicate-exon cluster to a three-duplicate-exon or a multiple-exon cluster. 22 Some complex alternative splicing has been achieved by expansion of the exon cluster through nonallelic homologous recombination.…”
mentioning
confidence: 99%
“…In particular, work conducted in different groups demonstrated that changes in the abundance of hnRNPs could modulate alternative splicing (Borah et al 2009;Nichols et al 2000;Olson et al 2007;Nilsen and Graveley 2010). Though the molecular mechanism underlying this effect is not clearly understood, Valcarcel and colleagues recently provided evidence that the alternative splicing forms of the hnRNP Squid can contribute to sexspecific splicing during sex determination events (Hartmann et al 2011).…”
Section: Post-translational Modifications Of Hnrnps and Their Regulatmentioning
confidence: 99%
“…Grk, osk and nos and mRNAs are in orange, green and violet lines, respectively. stages to regulate the translation of neuronal mRNAs (Piper and Holt 2004;Martin 2005;Kalifa et al 2006;Olson et al 2007). Moreover, the hnRNP Hrb87F, in addition to its role in omega speckle formation as well as normal development and stress tolerance , is also widely involved in neuronal development.…”
Section: Roles In Neuromuscular Developmentmentioning
confidence: 99%